Multicultural Approach: A Strategy towards Transforming African Americans’ Social Status and Countering Racial Agenda in The Sellout by Paul Beaty - Ahmed, Abrar; Dur e Afshan; Farooq, Athar (Pakistan Journal of Humanities and Social Sciences, 2023)
Racial essentialists created race as a propaganda of racism and after realizing this, the oppressed community has taken its rise towards the zenith of social transformation and respect. Growing injustice and oppressive biasness of whiteness created zeal in black people to stand against marginalizing forces and counter prejudice around them. The paper aims at analyzing new journey of African Americans’ transformation towards multiculturalism by getting away with cultural particularism that is restricting their communal circle. This paper investigates their efforts to omit racial, social, and ethnic differences and create plural and multicultural society as source of withstanding their rejection and exclusion in the Sellout by Paul Beatty. The study is quantitative in nature and develops a framework through multicultural stance of postmodernism. The finding reveals that the novel presents the efforts of the protagonist of the novel and African Americans in countering biasness around them by striving for multicultural society by operating beyond any social, cultural, and racial differences.